Mechanical, morphology, crystallisation and melting behaviour of polypropylene composites reinforced by non-metals recycled from waste printed circuit boards. (21st April 2021) - Xiong, Xu; Ma, Libo; Zhang, Zhimiao; Yang, Haicun
ABSTRACT: In this work, the non-metals recycled from waste printed circuit boards (NPCBs) are used as the reinforcing filler for polypropylene (PP) composites. The effects of particle size, surface modification, compatibiliser and NPCB content are evaluated by the detailed investigation of mechanical, morphology, crystallisation and melting behaviour. Mechanical test results showed that NPCBs could increase the tensile and flexural strength of composites significantly, which is further confirmed by the strong interfacial adhesion in scanning electron microscopy (SEM) observation. Meanwhile, differential scanning calorimetry (DSC) results indicate the heterogeneous nucleation effect of NPCBs. The crystallisation temperature ( T c ), nucleation and crystallisation rate, and crystallinity of composites are all increased in the presence of NPCBs. The perfect degree of crystal, melting temperature ( T m ), and the thickness and size of PP wafers were all decreased. The above results present a high-value reuse of NPCBs in high-performance PP composites.